Understanding Emergency Care Delivery Through Computer Simulation Modeling. (21st September 2017) - Laker, Lauren F.; Torabi, Elham; France, Daniel J.; Froehle, Craig M.; Goldlust, Eric J.; Hoot, Nathan R.; Kasaie, Parastu; Lyons, Michael S.; Barg‐Walkow, Laura H.; Ward, Michael J.; Wears, Robert L.
Abstract: In 2017, Academic Emergency Medicine convened a consensus conference entitled, "Catalyzing System Change through Health Care Simulation: Systems, Competency, and Outcomes." This article, a product of the breakout session on "understanding complex interactions through systems modeling, " explores the role that computer simulation modeling can and should play in research and development of emergency care delivery systems. This article discusses areas central to the use of computer simulation modeling in emergency care research. The four central approaches to computer simulation modeling are described (Monte Carlo simulation, system dynamics modeling, discrete‐event simulation, and agent‐based simulation), along with problems amenable to their use and relevant examples to emergency care. Also discussed is an introduction to available software modeling platforms and how to explore their use for research, along with a research agenda for computer simulation modeling. Through this article, our goal is to enhance adoption of computer simulation, a set of methods that hold great promise in addressing emergency care organization and design challenges.